Current trends in take-out food consumption and its influencing factors among first-trimester pregnant women in Changsha - Sheng Teng; Yi Yang; Leshi Lin; Wenjuan Li; Li Li; Fang Peng; Xiao Gao; Dongmei Peng (BMC Public Health)
Abstract Background Take-out food consumption has adverse effects on public health, and previous studies have reported that frequent consumption of take-out food increases the risk of hypertension and heart disease. However, the status of take-out food consumption among pregnant women remains unclear. This study aimed to provide a comprehensive description of the present state of take-out food consumption among first-trimester pregnant women in Changsha and to investigate the factors influencing this behaviour. Methods We included 888 pregnant women in early pregnancy from a cross-sectional study (March–August 2022) conducted at Changsha Hospital for Maternal and Child Health Care, Hunan Province, China. Electronic questionnaires were administered during early antenatal check-ups. The questionnaire included demographic information, health and lifestyle behaviours, pregnancy-related information, take-out food consumption, and anxiety and depression scales. Statistical analyses were conducted using SPSS 18.0, including nonparametric Kruskal-Wallis H tests and multivariate ordinal logistic regression, to explore the factors influencing take-out food consumption by first-trimester pregnant women. Results In Changsha, 73.3% of pregnant women consumed take-out food during early pregnancy. The top three types of take-out foods commonly consumed were rice noodles or noodles (55.7%), Chinese fast foods (49.9%), and sugary drinks or desserts (37.4%). The results of multivariate ordinal logistic regression analysis revealed that pregnant women with depression symptoms (odds ratio [OR] = 1.65, 95% confidence interval [CI]:1.18–2.32), higher education level (OR = 1.88, 95%CI:1.23–2.88), and higher online time (OR = 1.50, 95%CI:1.11–2.03) consumed take-out food more frequently in early pregnancy than those without depression symptoms, lower education level, and lower online time. Conclusions Our study suggests that take-out food consumption is common among first-trimester pregnant women in Changsha. Education level, depression symptoms, and online time are risk factors that may potentially influence the consumption of take-out food during early pregnancy.